Governmental Political Policy and Out-of-School Children in Osun State, Nigeria - Amaka Emordi; Bamire F.B.; Ibukunoluwa Ruth Olufemi (PT Pro Panoramic Solution, 2026)
This study examines how government responses addressed out-of-school children in Osun State, Nigeria. Using an exploratory research design, data were collected through questionnaires, interviews with major stakeholders and civil society organisations, and reports. Data were analysed using frequency tables and thematic analysis and interpreted through the lens of systems theory. The findings identified O'Meals, the school policing system, and the establishment of Early Child Care Development (ECCD) centers, among others, as policies implemented by the state government for out-of-school children in Osun State. Results also showed that the government's specific responses to out-of-school children had effectively reduced the number of out-of-school children in the state by 13.9%, although some challenges were encountered during implementation. The study concluded that the Osun State government’s response had reasonably addressed the issue of out-of-school children in the state through the implementation of government policies such as O’Meals, school policing systems, establishment of early childhood care development, nomadic schools, and collaboration with major stakeholders